Violencia familiar en la/el adulta/o mayor: a partir de su propia mirada, de la familia y de enfermería - Yupanqui Vásquez, Carmen Yrene (2010)
The present doctoral thesis in nursing sciences, had object of study to the familiar violence in the older adult, since the conception that has herself/himself, the family and nursing in Chota – Cajamarca, and as object analyze these conceptions. The theoretical approach was based in the contribution of IRIARTE (1993), BREILH (1996), MINAYO (2006) and KEIKELAME (2000), about violence; by BUSTAMANTE (2004), in relation the family; the OPS (2003), refereeing to the woman/men older adult; by WALDOW (1998 – 2005); about the nursing. Care with qualitative approach, creative and sentient method; by CABRAL (1998); using the dynamics knowledge tree and calendar; realized in four meetings; totalizing 23 participants. To the data analysis it used the principles of speech analysis according to ORLANDI (2002). The results were based in the dialog between the women/men older adults, families, nurses and the investigator, and concluded that the conception about familiar violence in the women/men older adult is structuring two categories: social and the technique. The fist endorses the conception of the women/men oldest adults. The second out line the nurse’s conception, whose care in centered in the women/men decease oldest adults disease. Pointed to the older adults, the lack of love, understanding and esteem to a person being a producer of abuse, loneliness, imprisonment, disease and death, and witnessing violence is violence. The family, not understanding of his advanced age, forced labor, disrespect, neglect, isolation and conversation. Bering matched in the indifference and incomprehension. While nurses reported that the care is not integral, to violent older adults or higher and ethics training is necessary for care good.